The Role of Work Stress in Mediating Workload and Work Environment on Crew Performance PT. Indonusa Tenggara Marine - I Komang Budiasa; I Made Sara; Ni Wayan Siramiati (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2021)
Performance is the result of work seen form the quality and quantity achieved by an employee in carrying out his duties in accordance with the given responsibilities assigned to him. Work stress is a condition of tension that affects the emotions, thought processes and physical condition of an employee. Work stress arises where work demands exceed the person’s capacity to cope, moreover an employee’s self-discomfort to the surrounding work environment. This study aims to determine the role of work stress in mediating of workload and work environment on crew performance. There were 31 crews of PT. Indonusa Tenggara Marine who participated as the sample of study. Those sample was chosen using nonprobability sampling with saturated sampling method. Data analyzed using descriptive analysis and inferential analysis. Hypothesis tested using the Partial Least Square (PLS) application. The results showed that the workload had a positive and insignificant effect on crew performance, work environment had a positive and insignificant effect on crew performance, workload had a positive and significant effect on work stress, work environment had a negative and significant effect on work stress, work stress had a negative and significant on crew performance, the effect of workload and work environment on crew performance has been perfectly mediated by work stress.